2013
DOI: 10.1002/adma.201301167
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Performing Solution‐Processed Small Molecule:Perylene Diimide Bulk Heterojunction Solar Cell

Abstract: By combining the molecular donor p-DTS(FBTTh2 )2 with a readily produced perylene diimide acceptor we are able to achieve a power conversion efficiency of 3.0%, making this one of the most efficient non-fullerene organic solar cells to date. The reduced power conversion efficiency of the present system compared to the use of phenyl-C71 -butyric acid methyl ester as an electron acceptor is shown to primarily be related to a significant reduction in the internal quantum efficiency. These results indicate the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
230
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 255 publications
(238 citation statements)
references
References 31 publications
6
230
0
2
Order By: Relevance
“…The readers who are interested in other acceptors like polymers, nanocrystals, or perylene diimides are referred to some recent articles. [29][30][31][32][33][34] 2. From charge-transfer states to free charge carriers…”
Section: Introductionmentioning
confidence: 99%
“…The readers who are interested in other acceptors like polymers, nanocrystals, or perylene diimides are referred to some recent articles. [29][30][31][32][33][34] 2. From charge-transfer states to free charge carriers…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] To this end, a few studies have qualitatively observed a positive correlation between increased structural order of donor molecules and hole mobility in SSM BHJ fi lms. [ 1,2,[16][17][18] However, the lack of a quantitative link between structural order and charge carrier mobility makes comparisons between material systems diffi cult and limits insights about how best to improve materials. A recent report also found that crystallization of the donor material can drive phase separation in SSM BHJ fi lms thereby enhancing the electron mobility as well-presumably due to enhanced connectivity of electron…”
mentioning
confidence: 99%
“…Compared with fullerene acceptors, nonfullerene acceptors present some advantages, such as broad and strong absorption, adjustable LUMO energy levels, and long‐term stability. In recent years, FF‐OSCs developed quickly21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42 and achieved PCEs of up to 6.8% 25…”
mentioning
confidence: 99%